2015
DOI: 10.1177/0003489415575059
|View full text |Cite
|
Sign up to set email alerts
|

Deafness Gene Variations in a 1120 Nonsyndromic Hearing Loss Cohort

Abstract: We performed a large number of MPS analyses and clarified the genetic background of Japanese patients with hearing loss. This data set will be a powerful tool to discover rare causative gene mutations in highly heterogeneous monogenic diseases and reveal the genetic epidemiology of deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 29 publications
2
27
0
2
Order By: Relevance
“…The largest comprehensive study to date, by Nishio and Usami, reported a diagnostic rate of ~40% in 1120 Japanese patients [33**]. Of the 112 genes these authors targeted with TGE+MPS panels, 30 genes were reported as deafness-causing in their cohort.…”
Section: Diagnostic Ratementioning
confidence: 99%
“…The largest comprehensive study to date, by Nishio and Usami, reported a diagnostic rate of ~40% in 1120 Japanese patients [33**]. Of the 112 genes these authors targeted with TGE+MPS panels, 30 genes were reported as deafness-causing in their cohort.…”
Section: Diagnostic Ratementioning
confidence: 99%
“…We also have recently reported that target exon sequencing using MPS is a powerful tool for the identification of rare gene mutations in deafness patients[68]. …”
Section: Introductionmentioning
confidence: 99%
“…Among a number of deafness-related genes (the Hereditary Hearing Loss Homepage, http://hereditaryhearingloss.org/), mutations in GJB2 , SLC26A4 , GJB3 , and mitochondrial 12S rRNA gene ( MT-RNR1 ) are found to be more frequent. Mutations in GJB2 and SLC26A4 have been reported to cause autosomal recessive nonsyndromic hearing loss, while the inheritance pattern of GJB3 mutations is not quite clear (Nishio and Usami, 2015). Mutations in these genes are estimated to explain more than 40% of non-syndromic hearing loss cases (Wu et al ., 2011, Qing et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%